RFCS PROJECT METHENERGY+ METHANE RECOVERY AND HARNESSING FOR ENERGY AND CHEMICAL USES AT COAL MINE SITES - Kamenik, Matjaž; Rošer, Janez; Ordonez, Salvador (Journal of Energy Technology, 2023)
Ventilation Air Methane emissions (VAM) from coal mines lead to environmental concern because of their high global warming potential and the loss of methane (CH4) resources. How to tackle methane harnessing and its use was studied and analysed in the scope of the RCFS project, which was performed from 2017 till 2020, and coordinated by the University of Oviedo in Spain within the scope of an international consortium of eleven entities from Poland, Spain, the United Kingdom, Czechia, Greece, Slovenia and Sweden, combining universities, research institutions and industry (mostly Polish mines and the Slovenian Velenje mine). The main challenge tackled in the project was the use of methane released from both operating and abandoned mines, which is an environmental and safety hazard and also a useful source of energy. Therefore, the effective extraction of methane, its enrichment, purification, separation, thermal or chemical upgrading, and its use, considering coal mine site specifics, was assessed. Despite good operational results, after in-depth economic analysis of the integration, CAPEX and OPEX calculation, there turned out to be a high economic dependence on the cost of adsorbent, since adsorption was the most promising technology for concentrating the methane in these emissions. Therefore, the economic viability depends on the development of materials that meet a minimum cost and performance. Within the scope of the project, a lot of activities were carried out in order to widen and exploit the results.